P1016Correlation between cardiac magnetic resonance-late gadolinium enhancement and electro-anatomical map for right atrium. (18th June 2020) - Gunturiz Beltran, C; Borras-Amoraga, R; Alarcon, F; Garre, P; Figueras, R; Caixal, G; Tolosana, J M; Arbelo, E; Roca, I; Prat, S; Perea, M J; Brugada, J; et al.
Abstract: Funding Acknowledgements: none Background: Electroanatomical map (EAM) detects areas of low voltage as a surrogated marker of fibrosis areas, being the reference technique for its detection. Cardiac magnetic resonance with Late Gadolinium enhancement (CMR-LGE) allows non-invasive detection of atrial fibrotic areas. CMR-LGE studies have focused on the left atrium since now. Purpose: We need to validate this test to extend its use to the right atrium (RA), since it is involved in the arrhythmogenic substrate of several arrhythmias, and probably also in atrial fibrillation (AF). Methods: Prospective observational study. Fifteen patients undergoing a first AF ablation procedure were included. All patients had a pre-procedural LGE-CMR performed. The blood pool-normalized intensity signal (image intensity ratio-IIR) was calculated for the right atrial wall, and values projected in a shell. IIR values validated for the left atrium were used to identify dense and intermediate fibrosis, and healthy tissue (>1.32, 1.2-1.32, <1.2, respectively). During the procedure but before ablation, a point-by-point high density EA bipolar voltage map of RA was obtained with a multipolar catheter. Standard voltage thresholds of 0, 1 mV and 0, 5 mV were used to characterize fibrotic and healthy tissue in EAM. For each RA, the EAM was projected into the IIR shell, and the correlation between bipolar voltage and normalized IIR values for each shell point was quantified. Then, we also obtained its concordance (categorical variables) according to the label automatically assigned by EAM/CMR with the pre-set thresholds: healthy tissue/ intermediate fibrosis/dense fibrosis. Results: A total of 8, 830 points were obtained, mean per patient 588 (± 509) points. A global weak negative correlation was found between the EA bipolar voltage map (EAM) and IIR (CMR) (r= -0.16, p < 0.0001)(figure). LGE-CMR identified more healthy tissue than EAM (81.0% vs 60.6% respectively), then CMR underestimated the fibrotic tissue in RA. Finally, we analyzed the concordance and we obtained that the degree of accuracy between both measurements was 55.7%. Conclusion: There was an inverse correlation between the bipolar voltage EAM and IIR (CMR) of low grade but with statistical significance. CMR underestimated fibrotic tissue in RA with respect to its identification by EAM.